Breast cancer statistics, 2017, racial disparity in mortality by state. (3rd October 2017) - DeSantis, Carol E.; Ma, Jiemin; Goding Sauer, Ann; Newman, Lisa A.; Jemal, Ahmedin
Abstract: In this article, the American Cancer Society provides an overview of female breast cancer statistics in the United States, including data on incidence, mortality, survival, and screening. Approximately 252, 710 new cases of invasive breast cancer and 40, 610 breast cancer deaths are expected to occur among US women in 2017. From 2005 to 2014, overall breast cancer incidence rates increased among Asian/Pacific Islander (1.7% per year), non‐Hispanic black (NHB) (0.4% per year), and Hispanic (0.3% per year) women but were stable in non‐Hispanic white (NHW) and American Indian/Alaska Native (AI/AN) women. The increasing trends were driven by increases in hormone receptor‐positive breast cancer, which increased among all racial/ethnic groups, whereas rates of hormone receptor‐negative breast cancers decreased. From 1989 to 2015, breast cancer death rates decreased by 39%, which translates to 322, 600 averted breast cancer deaths in the United States. During 2006 to 2015, death rates decreased in all racial/ethnic groups, including AI/ANs. However, NHB women continued to have higher breast cancer death rates than NHW women, with rates 39% higher (mortality rate ratio [MRR], 1.39; 95% confidence interval [CI], 1.35‐1.43) in NHB women in 2015, although the disparity has ceased to widen since 2011. By state, excess death rates in black women ranged from 20% in Nevada (MRR, 1.20; 95% CI, 1.01‐1.42) to 66% in Louisiana (MRR, 1.66; 95% CI, 1.54, 1.79). Notably, breast cancer death rates were not significantly different in NHB and NHW women in 7 states, perhaps reflecting an elimination of disparities and/or a lack of statistical power. Improving access to care for all populations could eliminate the racial disparity in breast cancer mortality and accelerate the reduction in deaths from this malignancy nationwide.CA Cancer J Clin 2017;67:439‐448. ©2017 American Cancer Society.